Mercury: the beginnings in the medicalization of common names of medicinal plants in Brazil - Bruno Vilson Leal Siqueira; Cássia Mônica Sakuragui; Bruno Eleres Soares; Danilo Ribeiro de Oliveira (Rodriguésia, 2020)
Abstract Medicalization of common names of medicinal plants is a process that involves replacing popular native names by trademarked names of drugs, active principles or therapeutic indications used by modern biomedicine. In Brazil, this process seems to have been intensified in the early 2000s due to the increasing use of those names in ethnoscientific surveys in local communities. In this study, we aimed to trace the origins of that process. For this purpose, we reviewed data from the “grey literature” pre-1980, including 15 books, compendia, dictionaries, and guides of medicinal plants. Mercury and its lexical changes were the only medicalized names found in the literature before the 1980s. This is probably due to the ancient use of mercury in several medical systems through human history, including by Brazilian apothecaries since the seventeenth century. Moreover, Mercurochrome was the name of a Brazilian trademark of antiseptic that probably influenced the use of medicalized names of mercury in the past. The name “Mercury” and its “natural” epithet combinations, like “Mercúrio-vegetal” (Mercury-plant) and “Mercúrio-do-campo” (Field-mercury), could have been the original medicalized way of naming medicinal plants in Brazil.